2014
DOI: 10.1177/0192623313519874
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Multiwalled Carbon Nanotubes Modulate the Immune Response of Trimellitic Anhydride–induced Chemical Respiratory Allergy in Brown Norway Rats

Abstract: The interaction between exposure to nanomaterials and existing inflammatory conditions has not been fully established. Multiwalled carbon nanotubes (MWCNT; Nanocyl NC 7000 CAS no. 7782-42-5; count median diameter in atmosphere 61 + 5 nm) were tested by inhalation in high Immunoglobulin E (IgE)-responding Brown Norway (BN) rats with trimellitic anhydride (TMA)-induced respiratory allergy. The rats were exposed 2 days/week over a 3.5-week period to a low (11 mg/m 3 ) or a high (22 mg/m 3 ) concentration of MWCNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Cell proliferation tests showed that a high concentration of MWCNTs decreased the proliferation of both HFLSs and RAW264 cells, while the same concentration of CB did not. Various studies have examined the inhibition of RAW264 cell proliferation by MWCNTs, including the influence of phagocytosis 22 23 . In this study, we showed that HFLS proliferation was inhibited slightly by 10 μg/mL MWCNTs and to 64% at 100 μg/mL MWCNTs, which was lower than that observed in RAW264 cells (18% inhibition at 100 μg/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation tests showed that a high concentration of MWCNTs decreased the proliferation of both HFLSs and RAW264 cells, while the same concentration of CB did not. Various studies have examined the inhibition of RAW264 cell proliferation by MWCNTs, including the influence of phagocytosis 22 23 . In this study, we showed that HFLS proliferation was inhibited slightly by 10 μg/mL MWCNTs and to 64% at 100 μg/mL MWCNTs, which was lower than that observed in RAW264 cells (18% inhibition at 100 μg/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly in one of these studies it was seen that MWCNTs induced inflammasome activation and subsequent IL-1β production by human THP-1 macrophages in vitro , which was suppressed by the T H 2 cytokines IL-4 and IL-13, which are present in the allergic asthma environment [59]. CNTs have also been looked at in a chemically induced asthma model by using trimellitic anhydride (TMA) to induce allergy in rats [60]. MWCNTs were administered after sensitization and challenge with TMA and unlike all the above discussed studies, actually decreased TMA-induced serum IgE levels and BALF lymphocytes [60].…”
Section: Enm-induced Asthma Exacerbationsmentioning
confidence: 99%
“…CNTs have also been looked at in a chemically induced asthma model by using trimellitic anhydride (TMA) to induce allergy in rats [60]. MWCNTs were administered after sensitization and challenge with TMA and unlike all the above discussed studies, actually decreased TMA-induced serum IgE levels and BALF lymphocytes [60]. …”
Section: Enm-induced Asthma Exacerbationsmentioning
confidence: 99%
“…On the other hand, large MWCNTs agglomerates/aggregates, which are found in granulomas in the allergic rats, decrease serum IgE levels and the number of lymphocytes in bronchoalveolar lavage. This event indicates the modulatory action of MWCNTs in the allergy-associated immune response (Staal et al, 2014). Thus, the diverse abilities of CNT to impact the immune system should be taken into consideration for hazard assessment (Fujita et al, 2015;Rydman et al, 2014).…”
Section: Carbon Nanotubesmentioning
confidence: 99%